ID: 36. Issue 1 (November 2015) - Garg, Abhishek; Amatya, Nilesh; Chen, Kong; Agustin Cruz, J.; Grover, Prerna; Whibley, Natasha; Conti, Heather R.; Mir, Gerard Hernandez; Sirakova, Tatiana; Childs, Erin C.; Smithgall, Thomas E.; Biswas, Partha S.; et al.
<x xml:space="preserve">Abstract</x> IL-17A (IL-17) is a proinflammatory cytokine that mediates host defense against extracellular pathogens but also contributes to the pathogenesis of various autoimmune diseases. Despite advances in our understanding of IL-17 signal transduction mechanisms, it is far less clear how IL-17R activity is kept in check to prevent harmful bystander inflammation. In an effort to identify novel, physiologically relevant regulators of IL-17 signal transduction, we evaluated microarray data of IL-17RA-dependent genes that mediate antifungal immunity. We thus identified the gene Zc3h12a (encoding MCPIP1/Regnase-1) as a possible feedback restriction element. MCPIP1 is an endoribonuclease (RNase) that inhibits TLR signaling in part by degrading cytokine mRNA transcripts such as Il6. Since IL-17 and TLR pathways share multiple target genes including Il6, we investigated the role of MCPIP1 in IL-17 signal transduction. Here, we demonstrate that MCPIP1 is upregulated by IL-17 and serves as a potent feedback inhibitor of IL-17 signal transduction. IL-17 signaling inhibition required MCPIP1's RNase activity, but not its deubiquitinase activity. In vivo, resistance to disseminated Candida albicans infection was enhanced in MCPIP1 haploinsufficient mice; resistance was reversed in an IL-17R-deficient background. Conversely, IL-17-dependent pathology in MCPIP1+/− mice was dramatically exacerbated during EAE and pulmonary inflammation. In vitro, MCPIP1 strongly inhibited the Lcn2 promoter activation by regulating the mRNA stability of the I<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qj5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />κ</alternatives>B<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kzq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ζ</alternatives> transcription factor. Unexpectedly, MCPIP1 also degraded Il17ra and Il17rc mRNA, independently of the 3' UTR. The cumulative impact of MCPIP1 on IL-6, I<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qj5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />κ</alternatives>B<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kzq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ζ</alternatives> and possibly IL-17R subunits results in a biologically relevant inhibition of IL-17 signaling.